THE OLDEST ESCHRICHTIID MYSTICETE AND A NEW MORPHOLOGICAL DIAGNOSIS OF ESCHRICHTIIDAE (GRAY WHALES) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
A close inspection of the dentary of Eschrichtius robustus (Cetacea, Mysticeti, Eschrichtiidae) revealed a peculiar organization of the coronoid region. Similar morphologies have been observed in two specimens which are respectively from the Early Pliocene of Piedmont and the Late Miocene of Apulia, Italy. The peculiar organization of the coronoid region consists of the presence of a satellite process parallel or slightly anterior to the coronoid process with a groove interposed between them. The morphology of the dentary is used here to emend the diagnosis of the family Eschrichtiidae and for including the above Italian specimens in this family. Such an emendation is due to the unique mandibular organization shared by Eschrichtius robustus and the Italian specimens mentioned above. The new diagnosis allows the establishment of the new genus Archaeschrichtius from the Late Miocene of Apulia, which represents the oldest eschrichtiid mysticete to be formally described up to now. Italian specimens extends back to the Late Miocene the fossil record of Eschrichtiidae and document aspects of feeding evolution within Eschrichtiidae for the first time.
Keywords: Dentary; Eschrichtiidae; Italy; Miocene; Mysticeti